Consumer‟s preference towards organic food products - M, Rupesh Mervin; R, Velmurugan (Journal of Management and Science, 2011)
The market of organic products is growing as the number of people willing to consume organic food and consumer preference towards organic food products is ever increasing. The promotion of organic food products constitutes an important option not only for producers, government and consumers but also to respond to societies‘ desire for higher food quality and food production that is less damaging to environment systems and improve the quality of life; this makes the study of consumer preferences highly important. The main purpose of this study is to identify the factors influencing consumer preferences toward organic products. The target population in this research includes consumers of Kozhikode district of Kerala state of India. By making use of convenience sampling method 750 respondents have been selected. Data required for the study have been collected with the help of questionnaire.The finding of the research work revealed that gender, age, occupation, monthly income, family status, level of awareness, state of health and environmental engagement are associated with consumer preference towards organic foods. The research work shows increasing monthly income and environment engagement activities influences consumer preference towards organic food products.There is an inverse relationship between consumer awareness and consumer preferences towards organic food. Organic food considered as healthy product and it is more preferred by the green consumers. The research result suggest that Government and social organizations have to promote organic farming at the households among general public and to take necessary steps for creating a regulatory system for authenticated organic certification and labeling in order to build-up the trust and confidence in consuming organic food products.